2016
DOI: 10.1111/ane.12551
|View full text |Cite
|
Sign up to set email alerts
|

No relevant midbrain atrophy in Parkinson's disease

Abstract: Mild midbrain atrophy is present in PD and can be detected with MRI. However, the midbrain atrophy in PD is not associated with the level of striatal dopaminergic dysfunction, and midbrain measurements therefore cannot be used as a clinically useful predictor of dopamine function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…1 Various PET tracers are available to evaluate the movement dysfunction in patients with MSA. 3,4 In some isolated neuropathologically confirmed MSA cases, DAT imaging can be either normal or decreased consistent with various clinical manifestations, suggesting heterogeneity of DAT distribution in MSA patients. DAT is a sodium-dependent facilitated diffusion transporter on the presynaptic membranes of dopaminergic nerve terminals.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1 Various PET tracers are available to evaluate the movement dysfunction in patients with MSA. 3,4 In some isolated neuropathologically confirmed MSA cases, DAT imaging can be either normal or decreased consistent with various clinical manifestations, suggesting heterogeneity of DAT distribution in MSA patients. DAT is a sodium-dependent facilitated diffusion transporter on the presynaptic membranes of dopaminergic nerve terminals.…”
mentioning
confidence: 99%
“…Molecular neuroimaging of the DAT defines integrity of dopamine terminals and provides a measurement to further aid diagnosis of uncertain parkinsonism. 3,4 In some isolated neuropathologically confirmed MSA cases, DAT imaging can be either normal or decreased consistent with various clinical manifestations, suggesting heterogeneity of DAT distribution in MSA patients. Previous imaging studies suggested that striatal DAT binding patterns differ in MSA-P and MSA-C. [5][6][7] However, there is still a need for larger samples sizes with added focus to clarify this disparity.…”
mentioning
confidence: 99%
“…There are several possible interpretations for these discrepancies. First, in PD patients only slight midbrain atrophy has been detected, and there is no correlation between midbrain atrophy and striatal dopamine function (Makinen et al, 2016). As a potential precursor of PD, iRBD is thus believed to present mild midbrain atrophy or even no atrophy.…”
Section: Discussionmentioning
confidence: 99%